2000
DOI: 10.1006/viro.2000.0498
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of the Late Gene Cluster from Lactobacillus Phages

Abstract: Three prophage sequences were identified in the Lactobacillus johnsoni strain NCC533. Prophage Lj965 predicted a gene map very similar to those of pac-site Streptococcus thermophilus phages over its DNA packaging and head and tail morphogenesis modules. Sequence similarity linked the putative DNA packaging and head morphogenesis genes at the protein level. Prophage Lj965/S. thermophilus phage Sfi11/Lactococcus lactis phage TP901-1 on one hand and Lactobacillus delbrueckii phage LL-H/Lactobacillus plantarum pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…The 2-Mb chromosome of the gut commensal Lactobacillus johnsonii NCC 533 (Nestlé) contained two prophages showing the genome organization of Sfi11-like pac-site Siphoviridae (54). The lysogeny module of these prophages contained more genes than are commonly found in temperate phages of LAB (128).…”
Section: Lactobacillusmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2-Mb chromosome of the gut commensal Lactobacillus johnsonii NCC 533 (Nestlé) contained two prophages showing the genome organization of Sfi11-like pac-site Siphoviridae (54). The lysogeny module of these prophages contained more genes than are commonly found in temperate phages of LAB (128).…”
Section: Lactobacillusmentioning
confidence: 99%
“…Comprehensive research was conducted on two virulent phages of the soil bacterium Bacillus subtilis: phi29, a podovirus, and SPP1, despite its life-style a typical Sfi11-like siphovirus (54) and by far the best-characterized phage of this proposed phage genus (see references 6 and 130 for recent examples and references therein). Much less is known about temperate B. subtilis phages, which have been classified into five groups (231).…”
Section: Bacillusmentioning
confidence: 99%
“…Until now only a single Sfi21-like phage was identified in the genus Lactobacillus. L. gasseri phage adh shared deduced amino acid sequence identity up to 61% with phage Sfi21 over the DNA packaging, head, tail, lysogeny, and DNA replication modules (22). The identical organization of the replication and lysogeny modules from L. casei phage A2 and phage Sfi21 (19,28,40,46) suggested that phage A2 is a further member of this group.…”
Section: Resultsmentioning
confidence: 98%
“…An intriguing observation was the fact that distinct Sfi21-like phage isolates were linked by a hierarchy of relatedness when S. thermophilus phages were used as a reference point (11). Sfi21-like phages from S. thermophilus were closely related at the DNA level essentially over the entire genome length (11); those from S. thermophilus and L. lactis shared a smaller degree of DNA identity limited to part of the structural genes (20); S. thermophilus and Lactobacillus gasseri Sfi21-like phages were related by a relatively high level of protein similarity over the structural genes, but significant DNA sequence homology was no longer detected (22). Notably, even Escherichia coli phage HK97 shared a functional gene map with Sfi21-like S. thermophilus phages over the structural genes in the absence of any sequence similarity (11).…”
mentioning
confidence: 99%
“…The location of transglycosylase motifs are indicated by the grey boxes. gpR1608 in phi g1e, a minor structural protein , is probably a tail tape measure protein (Desiere et al, 2000) and misannotated as a capsid protein.…”
Section: Morphogenesismentioning
confidence: 99%